Men having sex with men in Surakarta, Indonesia: demographics, behavioral characteristics and prevalence of blood borne pathogens - Prasetyo, Afiono Agung; Ariapramuda, Rabindra; Kindi, Ekkim A; Dirgahayu, Paramasari; Sari, Yulia; Dharmawan, Ruben; Kageyama, Seiji (Southeast Asian journal of tropical medicine and public health, 2014)
The objectives of this study were to investigate the prevalence of human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), hepatitis D virus (HDV), human T-lymphotropic virus types 1 and 2 (HTLV-1/2), Torque teno virus (TTV) and Toxoplasma gondii (T. gondii) infection among men who have sex with men (MSM) in Surakarta, Indonesia, and the risk factors and sexual behavior associated with these infections. A cross sectional study was performed from October 2009 to October 2011 among 143 MSM by face-to-face interviews to complete an interviewer-administered questionnaire. Subjects were tested for ,HIV, HBV, HCV, HDV, HTLV-1/2 and toxoplasma infection using serology and for TTV using molecular detection. The seropositive rates for anti-HIV, HBsAg, anti-HCV, anti-HDV, anti-HTLV-1/2, IgM anti-T. gondii, IgG anti-T, gondii and TTV DNA were 9.1%, 9.8%, 28.0%, 0.7%, 0.7%, 1.4%, 30.8%, and 26.6%, respectively. Risk factors associated with HIV infection were a history of injecting drug use (IDU) [adjusted OR (aOR) 6.0; 95% CI: 1.10-33.01] and a receptive role in sexual activity (aOR 8.1; 95% CI: 1.30-50.04) [corrected]. Having a tattoo (aOR 3.2; 95% CI: 1.28-7.98) and practicing both anal and vaginal sex without a condom (aOR 2.3; 95% CI: 1.06-4.92) were associated with toxoplasma infection. A history of IDU (aOR 32; 95% CI: 5.93-177.93) was associated with TTV infection. The subjects examined in this study were found to be infected with HIV, HBV, HCV, HDV, HTLV-1/2, TTV, and T. gondii. These infections were associated with high-risk behavior.